2014
DOI: 10.1182/blood-2014-02-554501
|View full text |Cite
|
Sign up to set email alerts
|

Murine coagulation factor VIII is synthesized in endothelial cells

Abstract: • Lman1 tissue-specific knockout mice reveal that endothelial cells, not hepatocytes, are the primary source of FVIII biosynthesis.• F8 gene expression is heterogeneous among endothelial cell populations in different tissues.The primary cellular source of factor VIII (FVIII) biosynthesis is controversial, with contradictory evidence supporting an endothelial or hepatocyte origin. LMAN1 is a cargo receptor in the early secretory pathway that is responsible for the efficient secretion of factor V (FV) and FVIII … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
145
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(158 citation statements)
references
References 60 publications
2
145
0
5
Order By: Relevance
“…Finally, it is worth noting that the liver is the key site of synthesis of most proteins required for the regulation of coagulation and fibrinolysis. Because hepatocytes and sinusoidal endothelial cells produce clotting and inhibitory factors that circulate in the bloodstream (41,42), liver injury and disease result in diminished production of these factors and subsequently a variety of coagulation disorders (7,43). Therefore, the plasmin-induced liver damage we detected in Chd4 fl/fl Lyve1-Cre + livers as early as E13.5 may contribute to the deficit of fibrin-rich LV thrombi we detected in those embryos.…”
Section: Methodsmentioning
confidence: 87%
“…Finally, it is worth noting that the liver is the key site of synthesis of most proteins required for the regulation of coagulation and fibrinolysis. Because hepatocytes and sinusoidal endothelial cells produce clotting and inhibitory factors that circulate in the bloodstream (41,42), liver injury and disease result in diminished production of these factors and subsequently a variety of coagulation disorders (7,43). Therefore, the plasmin-induced liver damage we detected in Chd4 fl/fl Lyve1-Cre + livers as early as E13.5 may contribute to the deficit of fibrin-rich LV thrombi we detected in those embryos.…”
Section: Methodsmentioning
confidence: 87%
“…5 On the other hand, transplantation of liver from hemophilic donors, either dogs 6 or humans, 7 into healthy subjects does not cause hemophilia, indicating that FVIII is also produced in extrahepatic sites. Recent studies using a cell therapy approach 8,9 or cell typespecific knockout experiments indicated that FVIII is produced largely in liver sinusoidal endothelial cells (LSEC); 10,11 although FVIII mRNA was present in endothelial cells of kidneys, spleen and lungs, it was absent in endothelial cells of the brain and heart. 10,[12][13][14][15] These findings were in agreement with studies showing that hemophilic patients benefited from transplantation of the spleen in the long-term.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, high expression of the HOXA9 gene is a highly significant marker of poor prognosis in acute myeloid leukemia, 1 and dysregulation of HOXA9 appears to play a central role in several distinct leukemias. These include acute myeloid leukemia and acute lymphoblastic leukemias caused by translocations of the Mixed Lineage Leukemia (MLL) gene, [2][3][4] fusions of the HOXA9 gene that produce a novel HOXA9-NUP98 fusion protein in acute myeloid leukemia, 5 and T-cell acute lymphoblastic leukemias that have translocations between the TCRβ and HOXA9/A10 loci. 6 Interestingly however, despite this seemingly central role in a subset of acute leukemias, Hoxa9 expression alone is only weakly oncogenic in mouse leukemia models and usually requires a second "hit" via overexpression of Meis1, 7,8 or in some cases Pbx3.…”
Section: What Are the Implications Of These Findings For Cellular Andmentioning
confidence: 99%
“…[4][5][6] The overall conclusion was that liver sinusoid endothelial cells (LSEC), not hepatocytes, are the main cellular source of hepatic factor VIII. Here, in a unique set of experiments, the authors demonstrated that transplant of non-parenchymal cells (a mix of Küpffer cells and LSEC), improved circulating factor VIII levels, but infusion of isolated hepatocyte did not.…”
mentioning
confidence: 99%
See 1 more Smart Citation